The Influence of the COVID-19 Pandemic on Mental Well-Being and Psychological Distress: Impact Upon a Single Country - Gray, Nicola S.; O'Connor, Chris; Knowles, James; Pink, Jennifer; Simkiss, Nicola J.; Williams, Stuart D.; Snowden, Robert J. (Frontiers in Psychiatry, 2020)
The COVID-19 pandemic is likely to have affected the psychological well-being and mental health of many people. Data on prevalence rates of mental health problems are needed for mental health service planning. Psychological well-being and prevalence of clinically significant mental distress were measured in a large sample from Wales 11–16 weeks into lockdown and compared to population-based data collected in 2019 before the COVID-19 pandemic. Data were collected using an online survey disseminated across Wales and open to adults (age 16+) from 9th June to 13th July 2020. Psychological well-being was indexed via the Warwick-Edinburgh Mental Well-being Scale, and psychological distress was indexed via the K10. Data from 12,989 people who took part in this study were compared to that from April 2018 - March 2019, gathered by the National Survey for Wales (N = 11,922). Well-being showed a large decrease from 2019 levels. Clinically significant psychological distress was found in around 50% of the population (men = 47.4%, women = 58.6%), with around 20% showing “severe” effects (men = 17.0%, women = 20.9%): a 3–4-fold increase in prevalence. Most affected were young people, women, and those in deprived areas. By June-July 2020 the COVID-19 pandemic had dramatic effects on the mental health of people living in Wales (and by implication those in the UK and beyond). The effects are larger than previous reports. This probably reflects that the current data were taken deeper into the lockdown period than previous evaluations. Mental health services need to prepare for this wave of mental health problems with an emphasis on younger adults, women, and in areas of greater deprivation.